Physicochemical and biological properties of tricalcium silicate-based reparative materials with alternative radiopacifiers and Biosilicate - Queiroz, Marcela Borsatto [UNESP] (2018)
Tricalcium silicate cements associated with radiopacifiers are used as repair materials. Publication 1: Evaluation of tricalcium silicate-based cements (TCS) associated with zirconium oxide (ZrO2), calcium tungstate (CaWO4) or niobium oxide (Nb2O5) radiopacifiers compared to MTA Repair HP (MTA HP). Publication 2: Evaluation of tricalcium silicate-based cements (TCS) associated with zirconium oxide (ZrO2) radiopacifier with 10% or 20% of Biosilicate (TCS ZrO2 + 10% Biosilicate and TCS ZrO2 + 20% Biosilicate) compared to Biodentine. Setting Time (ST) and radiopacity were evaluated based on ISO 6876/2002 standard. Solubility was evaluated according to the method proposed by Carvalho-Júnior et al. (2007) modified. pH was measured at 3, 12 and 24 hours and 7, 14 and 21 days after immersion in distilled water. Cellular cytotoxicity and bioactivity were evaluated by methyltetrazolium (MTT), neutral red (NR), alkaline phosphatase (ALP), alizarin red (ARS) and real time PCR (qPCR) (Publication 1) assays in different periods of contact with eluates of the materials in Saos-2 cells. Antibacterial activity was evaluated by direct contact on Enterococcus faecalis in the planktonic form. For the physico-chemical and ARS tests, the data were submitted to ANOVA and Tukey tests; for MTT, NR and ALP tests the data were analyzed by the Two-Way ANOVA and Bonferroni tests; the antibacterial activity, were submitted to Kruskall-Wallis and Dunn tests (α = 0.05). Publication 1: TCS + CaWO4 presented the highest setting time and MTA HP the lowest (p<0.05). Except for TCS, all materials presented radiopacity above 3 mm Al. The materials presented solubility in accordance with ISO 6876/2002. The cements evaluated presented alkaline pH values in all periods. The materials were cytocompatible at the dilution of 1:8. The highest ALP activity occurred in 14 days for all the cements, especially TCS, TCS + ZrO2 e TCS + CaWO4 when compared with the negative control (NC). TCS + Nb2O5 presented higher formation of mineralization nodules in comparison with the NC (p<0.05). After 7 days, there was no statistically significant difference (p>0.05) in mRNA expression for ALP, when compared to NC. However, after 14 days there was na overexpressed ALP mRNA, especially TCS + Nb2O5 (p<0.05), in relation to the CN. All the materials TCS presented antimicrobial action against E. faecalis. Publication 2: TCS presented the highest setting time (p<0.05) and the other materials presented no statistical difference (p<0.05). TCS ZrO2 + 10% Biosilicate and TCS ZrO2 + 20% Biosilicate showed radiopacity and solubility in accordance with ISO 6876/2002. All materials presented alkaline pH in the different periods. In the MTT and NR assays, the materials presented no cytotoxic effects, except for Biodentine that presented lower cell viability compared with the NC at the lower dilutions (1:1 and 1:2). The highest ALP activity was observed in the period of 14 days, with emphasis on TCS cements and Biodentine. All the materials TCS and Biosilicate presented antimicrobial action against E. faecalis. It could be concluded that tricalcium silicatebased cement associated with different radiopacifiers presented proper physicochemical properties, bioactive potential and was non-cytotoxic in Saos-2, suggesting a potential use as a repair material (Publication 1). Biosilicate in two proportions, associated with TCS and ZrO2, presented proper physicochemical properties and no cytotoxic effect. Therefore, this material showed perspectives for clinical application (Publication 2).